2019
DOI: 10.1002/ajim.23053
|View full text |Cite
|
Sign up to set email alerts
|

Patient care aides: Differences in healthcare coverage, health‐related behaviors, and health outcomes in a low‐wage workforce by healthcare setting

Abstract: Objectives: Patient care aides, who provide basic care to patients in a variety of healthcare settings, have been observed to have higher prevalences of adverse health metrics than the general US workforce. However, few studies have examined how healthcare access and health behaviors and outcomes among patient care aides differ by work setting (home health, nursing home, and hospital).Methods: Data from the 2013 to 2016 Behavioral Risk Factor Surveillance System were used to assess the prevalences of healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 26 publications
(32 reference statements)
0
28
1
Order By: Relevance
“…18 Consistent with this line of reasoning, another study found that unionized certified nursing assistants working in nursing homes were far more likely than the HHAs in this study to cite their employer as a primary source for COVID-19-related information. 19 The findings on frequent experiences of physical fatigue and emotional exhaustion accord with research documenting high levels of stress and burnout among HHAs, 7,20 and the greater difficulties HHAs reported taking care of their physical and mental health amid the pandemic build on recent work showing increased stress among health care workers during this period. 21,22 For the HHAs in our study, heightened stress may be linked to the concerns participants expressed about exposing themselves, family, and patients to COVID-19.…”
Section: Discussionmentioning
confidence: 58%
“…18 Consistent with this line of reasoning, another study found that unionized certified nursing assistants working in nursing homes were far more likely than the HHAs in this study to cite their employer as a primary source for COVID-19-related information. 19 The findings on frequent experiences of physical fatigue and emotional exhaustion accord with research documenting high levels of stress and burnout among HHAs, 7,20 and the greater difficulties HHAs reported taking care of their physical and mental health amid the pandemic build on recent work showing increased stress among health care workers during this period. 21,22 For the HHAs in our study, heightened stress may be linked to the concerns participants expressed about exposing themselves, family, and patients to COVID-19.…”
Section: Discussionmentioning
confidence: 58%
“…These include the inability to practice physical distancing at work or to work from home, low wages, lack of paid sick leave, reliance on public or shared transportation, crowded housing, limited access to health care, and the need to hold multiple jobs (3,5,6). Several of these inequities also hinder management of underlying conditions that increase the risk for severe COVID-19 (7). These inequities also pertain to groups of essential workers not assessed in this report because of inadequate sample size (e.g., low levels of health care access among food preparers/servers, agricultural workers, and building/grounds maintenance and support, including housekeepers and janitors in health care) (8).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, COVID-19 vaccination of HC aides is a high priority. It is concerning therefore that aides have had low rates of vaccination against seasonal flu [ 8 ••]. Along with medical considerations, effective vaccination programs need to address the economic and social determinants of HC aide infection risks, their access to vaccinations, and their concerns about accepting vaccinations [ 8 ••, 87 ].…”
Section: Infection Hazardsmentioning
confidence: 99%
“…The importance of home-based care as an alternative to facility-based care was underscored when the COVID-19 pandemic began: elders were at high risk of severe COVID-19 infection [ 1 ], and nursing homes had high infection rates [ 2 5 ]. At the same time, most of the HC workforce is composed of aides, who also are vulnerable to COVID-19 due to their work exposures and to their experience of social and economic inequities (housing where social distancing is not possible, limited health care access) that present infection risks [ 6 , 7 , 8 ••, 9 ]. Many elders were afraid to have aides enter their homes, and many aides were concerned about caring for those with COVID-19 in the home-work environment where infection prevention measures were not well established [ 10 ••].…”
Section: Introductionmentioning
confidence: 99%